The phenomenon of fandom consumption in k-pop commodity through the army community : Bangtan Sonyeondan fandom - Farhana Dinningrum, Rania; Umi Satiti, Nur Latifah (COMMICAST, 2022)
The appearance of ARMY as a loyal fans is a response to what BTS has to offer as a K-Pop idols. Aside being a fan, their consumption behavior is inevitable. Along with the development of media technology and as a result of pop culture commodities, fans create its own meaning and culture as an active actor of consumption. This research provides an overview of the way consumption culture is formed in ARMY fandom and how it affects most significant aspects in their life. The researcher also wants to examine related to the concept of free fan labor that fans holds such an important role at maintaining the fan production culture in the web and benefit the K-Pop industry to broaden their market globally. This research uses a qualitative method. Then the researcher collects data by interviewing six informants who have consume BTS merchandise continuously with purposive sampling technique. The result of this research showed that fans consistently interpret the goods they consumed, the value they generate from their sense of closeness to BTS members. This research also demonstrated regarding fans becoming “free” fan labor with their own eagerness, along with the fan production culture results to the personalize customization into their own interest as an active and loyal costumer, with the exchange of pleasure they got from actively interact and exchanging feedback with another fans in the cyberspace.